Phân tích thư mục về chứng chỉ vi mô trong giáo dục đại học dựa trên dữ liệu từ Scopus - Nguyễn Việt Hồng, Nguyễn Việt Hồng; Nguyễn Thị Minh Ngọc, Nguyễn Thị Minh Ngọc (Tạp chí Giáo dục, 2026)
Micro-credentials are emerging as a disruptive trend in global higher education, meeting the needs of flexible learning and rapid skill enhancement for learners. However, in Vietnam, this concept is still relatively new. This study conducted a systematic review combined with bibliometric analysis to draw a comprehensive picture of the field of micro-credential research in higher education worldwide. By applying the PRISMA 2020 methodology, we screened and selected 108 scientific works from the Scopus database in the period from 2015 to 2025 for analysis. VOSviewer software was used to visualise the collaboration network between authors, countries and prominent research topics. The results showed a sharp increase in the number of publications since 2021, with Australia leading the way in both quantity and impact. Eight main research clusters were identified, highlighting issues related to the design and implementation of micro-credentials, lifelong learning, digital badges, and the impact of micro-credentials on the education system. The study also identified the most influential authors and works that shaped the main academic debates in the field. This paper not only provides a systematic scholarly map but also offers important implications for education managers, policy makers, and researchers in Vietnam in orienting the development and application of micro-credentials.